ANALISA YANG MEMPENGARUHI KEPUTUSAN TENAGA KESEHATAN MELAKUKAN VAKSINASI COVID-19 DOSIS LANJUTAN (BOOSTER) - Muhammad Win Arami; Novianti Purnamasari; Sri Rahayu (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
The Covid-19 pandemic is not over yet. The development of viral mutations produces new variants that result in a decrease in effectiveness of previous vaccines. The provision of the a futher dose of Covid-19 Vaccine (Booster) to health workers is an effort to maximize protection for health worker. The study uses a qualitative with phenomenological approach. The sample selection was done purposively with 7 people as informants. The result showed that motivation knowledge perception and support from the government had a major influencing the decision of health workers to carry out futher dose of va